104 The Natural Course of Moyamoya Disease in Patients With Prior Hemorrhagic Stroke: Clinical Outcome and Risk Factors for Recurrent Stroke. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Zhao, Jizong; Liu, Xingju; Zhang, Dong
Abstract: INTRODUCTION: To evaluate the incidence of recurrent intracranial bleeding and mortality in patients with hemorrhagic moyamoya disease (MMD), and to identify risk factors and the time course of these events. METHODS: A total of 128 patients with complete follow-up treated conservatively were included. The occurrence of recurrent stroke over long-term follow-up was documented. Annual and cumulative incidence rate of rebleeding was generated via Kaplan Meier survival analysis, and risk factors for rebleeding were analyzed through Cox proportional hazards regression models. RESULTS: The median follow-up time was 10.1 (range:1-27) yr. During 1300.7 patient-years, 47(36.7%) patients experienced 59 episodes of rebleeding, rendering an average annual incidence of 4.5%. Among them, 9 patients (19.1%) died from rebleeding and 12 patients had serious disability (modified Ranking Scale = 3). The cumulative risk of rebleeding was 7.8% at 5 yr, 22.6% at 10 yr, and 35.9% at 15 yr. Only 4 (3.1%) patients experienced ischemic stroke, yielding an average annual incidence of 0.3%. Decrease of regional cerebral blood flow (rCBF) (HR, 2.23; P = .03), smoking, and drinking history (HR, 2.43; P = .04) were independent predictors of rebleeding. Rebleeding (HR, 10.76; P = .02) and hypertension (HR, 5.29; P = .02) were associated with increased mortality. Age, types of first bleeding, digital subtraction angiography stage, family history, and coexistent with cerebral aneurysms were not associated with any increased risk of rebleeding. CONCLUSION: Rebleeding events were common in patients with hemorrhagic MMD and the risk of rebleeding increased within a very long-term follow-up. Rebleeding was strongly associated with increased mortality. Decrease of rCBF, smoking, and drinking history seem to be risk factors for rebleeding.